Correction: Externally controlled drug release using a gold nanorod contained composite membrane. Issue 44 (1st November 2016) - Kim, Kibeom; Jo, Min-Chul; Jeong, Sundo; Palanikumar, L.; Rotello, Vincent M.; Ryu, Ja-Hyoung; Park, Myoung-Hwan
Abstract : Correction for 'Externally controlled drug release using a gold nanorod contained composite membrane' by Kibeom Kim, et al., Nanoscale, 2016, 8, 11949–11955.